2004
DOI: 10.1111/j.1440-1827.2004.01633.x
|View full text |Cite
|
Sign up to set email alerts
|

Parachordoma is not distinguishable from axial chordoma using immunohistochemistry

Abstract: Parachordoma is a rare soft tissue tumor that morphologically resembles chordoma of the axial skeleton but occurs in a peripheral site. A recent study reported immunohistochemical differences between chordoma and parachordoma. While both tumors were positive for cytokeratin (CK) 8/18 (as recognized by the antibody Cam5.2), S100 and epithelial membrane antigen (EMA), only the chordoma was positive for CK7, CK20, CK 1/5/10/14 (as recognized by the antibody 34betaE12) and carcinoembryonic antigen (CEA). It has si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…9 Extraskeletal soft-tissue chordoma does exist, is extremely rare, and is histologically, immunohistochemically and behaviorally distinct from parachordoma, the former having metastatic potential that is absent in the latter. 9,15 The distinction between chordoma and parachordoma also takes on clinical significance in humans, as the former is invasive and likely to recur following surgical excision. It should be noted, however, that post-resection local recurrence of parachordomas has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Extraskeletal soft-tissue chordoma does exist, is extremely rare, and is histologically, immunohistochemically and behaviorally distinct from parachordoma, the former having metastatic potential that is absent in the latter. 9,15 The distinction between chordoma and parachordoma also takes on clinical significance in humans, as the former is invasive and likely to recur following surgical excision. It should be noted, however, that post-resection local recurrence of parachordomas has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that post-resection local recurrence of parachordomas has been reported. 15 Gastrointestinal involvement by parachordoma is uncommon in humans, with only a single report of a primary tumor in the gastric serosa. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those authors also noted that chordomas expressed similar antigens and also CK 1/10, which parachordomas did not. Scolyer et al (2004) determined that parachordomas and chordomas may not be easily distinguished immunohistochemically because of the overlap in reactivity between the tumours and the differences in individual variability within a tumour type. New Zealand Veterinary Journal 57(5), 2009 301 In summary, the tumour reported here had features consistent with parachordomas reported in people.…”
Section: Discussionmentioning
confidence: 99%
“…While immunohistochemistry is useful for excluding epithelial and mesenchymal tumours, recent studies have indicated that parachordomas are not easily distinguished from chordomas despite the use of these markers (Scolyer et al 2004).…”
Section: Introductionmentioning
confidence: 99%